1980
DOI: 10.1073/pnas.77.7.4354
|View full text |Cite
|
Sign up to set email alerts
|

Comparative airway and vascular activities of leukotrienes C-1 and D in vivo and in vitro.

Abstract: The pharmacologic activities of leukotrienes C-i and D (LTC-1 and LTD), constituents of slow reacting substance of anaphylaxis (SRS-A), were evaluated in vitro on airway contractile tissues and in vivo on pulmonary mechanical function, mean systemic arterial pressure, and cutaneous microcirculation. In vitro both LTC-Land LTD were potent and selective peripheral airway agonists, being more active than histamine; furthermore, LTD was active on peripheral airways at concentrations 1/100th those of LTC-1. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
189
2
5

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(202 citation statements)
references
References 16 publications
5
189
2
5
Order By: Relevance
“…Minimal fluorescence (F min ) was determined by subsequent addition of the chelator EGTA in Tris-HCl buffer (100 mM, pH 9.0) at 125 mM. Stimuli consisted of LTD 4 , LTB 4 , and platelet-activating factor (PAF; Cayman Chemicals, Ann Arbor, MI).…”
Section: Intracellular Calcium Mobilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimal fluorescence (F min ) was determined by subsequent addition of the chelator EGTA in Tris-HCl buffer (100 mM, pH 9.0) at 125 mM. Stimuli consisted of LTD 4 , LTB 4 , and platelet-activating factor (PAF; Cayman Chemicals, Ann Arbor, MI).…”
Section: Intracellular Calcium Mobilizationmentioning
confidence: 99%
“…LTD 4 -induced eosinophil infiltration of the airway could be blocked by the early cysLT antagonist MK-571 (15). More recently, in human studies, blocking the LTD 4 receptor has been shown to reduce airway eosinophil numbers in mildly uncontrolled asthma (16), suggesting it may be a contributing factor in lung eosinophilia in asthma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cysteinyl LTs (cys-LTs) induce bronchoconstrictor effects [6], increase mucus formation [7], and induce bronchial wall oedema [8]. LTB 4 stimulates neutrophil chemotaxis [9] and activates those cells, leading to the release of mediators and superoxides.…”
mentioning
confidence: 99%
“…Since the discovery of the slow reacting substance of anaphylaxis (SRS-A), which had been tentatively desig nated as p-LTs until identification of their structures, the p-LTs have been proven to be potent pulmonary tissue constrictors in some species, especially humans and guinea pigs (4)(5)(6)(7). Because human or guinea pig lungs possess a great ability for p-LT formation and their airway smooth muscles markedly respond to p LTs, p-LTs formed intrinsically may be largely re sponsible for the pulmonary tissue contractions during anaphylaxis.…”
mentioning
confidence: 99%